Perceived product quality, perceived value, customer satisfaction and their relation to brand loyalty - Mohd Kassim, Abdul Wahid; Igau, Oswald Aisat; Harun, Amran; Shamsudin, Abdul Shukor; Al-Swidi, Abdullah Kaid (2014)
There has been a substansial body of evidence to relate trust as an important component to business trends.The study of trust has been exponentially discussed in various forms and context which expands across broad fields and sciences.This paper aims to provide additional rationale and foundational support for the advancement of knowledge pertaining to trust and its relation to the adoption of open innovation. Based from the literature review, this paper view trust from the light of adoption of innovation studies to better understand how it can best used to measure the readiness to adopt open innovation.